Characteristics of dissolved organic matter in water bodies during the dry season in the Huainan section of the Huaihe River Basin in Northern Anhui Province, China - Kai Zhang; Xiaoli Kai; Liangmin Gao; Han Song; Lin Wu; Xin Shu; Zhendong Pang (Journal of Freshwater Ecology)
This study investigated the spatial heterogeneity of dissolved organic matter (DOM) composition and characteristics in the central reaches of the Huaihe River Basin. The dry season DOM content and composition of three river bodies (the main stream of Huaihe River, the Huaihe tributaries and agricultural drainage ditches) in the Huaihe River Basin were studied using UV-Vis and three-dimensional fluorescence spectroscopy combined with parallel factor analysis (EEMs-PARAFAC). The degree of DOM humification and the relative molecular weight of tributaries and agricultural drainage ditches were significantly higher than those of the main stream (p < 0.01), and regarding the autogenetic characteristics of the three types of water bodies the tributaries and drainage ditches were more strongly affected by exogenous interference than the main stream. Three kinds of chemical components were determined by PARAFAC mode(C1:terrsstrial humus-like;C2:tryptophan-like;C3:protein-like), protein-like components were the main fluorescent components in DOM during the dry season, the proportion of different water systems exceeds 50%. Principal component analysis (PCA) showed that the fluorescence intensity of humus was closely related to the TP(Total phosphorus) concentration in the Huainan section water body of the Huaihe River Basin during the dry season. The absolute principal component-multiple linear regression model showed that the contribution of water nutrition to the C2 and C3 of protein-like fluorescent components was greater, while exogenous interference had a greater effect on the TP physicochemical index.